Pengaruh Pandemi Covid 19 terhadap Tata Cara Ibadah serta Penggunaan Media Digital dalam Pelayanan Remaja di HKBP Jatiwaringin - Panuturi Sitompul; Djoys Anneke Rantung; Lamhot Naibaho (Journal on Education, 2023)
At first we were very sad and concerned because of technological constraints, because it has become a tradition that meetings must be face-to-face and direct. In a pandemic situation this cannot be done so worship must also be carried out remotely and using technology, the atmosphere of fellowship changes with distance and is united in digitalization or online worship and meetings. Specifically with teenagers, the presence of digital worship has made changes in their worship habits. By only using cellphones and laptops as well as television, they can worship anywhere. With digital worship, youth and congregations can praise God in joy, and they are increasingly familiar with online worship. And the focus of this descriptive research will be to examine the benefits of online worship and how it differs from in-person or online worship, then in a new atmosphere, the digitalization system will not be completely abandoned, but has become a necessity for the development of worship, especially for youth and adolescents. The results of observations, experiences and small research as well as descriptions will help youth and the church to make and review models of worship that are more actual in the digital age, so that youth worship is more actual and makes them more enthusiastic and grow in faith.